Pengaruh Pendekatan Behavioristik dengan Teori Kondisioning Klasik Terhadap Pembentukan Perilaku Anak Usia Dini - Sekar Ayu Pratiwi; Rizka Andriyani; Apri Sara Banjarnahor; Emmi Ayu Lestari; Riwayati Oktaria Pakpahan; Yeni Marito (Universitas Palangka Raya, 2024)
The development of educational psychology from the 19th to the 20th century witnessed significant advancements, marked by the emergence of various new theories, particularly the behaviorist learning theory introduced by Ivan Pavlov. Classical conditioning theory serves as an important foundation for understanding children’s behavior, especially in early childhood, where children are highly responsive to environmental stimuli. This study aims to explore the influence of a behaviorist approach through classical conditioning theory on the formation of early childhood behavior. The method employed is descriptive qualitative, focusing on interviews and observations. Findings indicate that conditioning can foster positive behaviors, enhance reading interest, and alleviate discomfort in the learning process. The activity “Missing Numbers” is implemented to develop fine motor skills while introducing the concept of numbers. The results show that children who participated in this activity experienced improvements in number recognition and fine motor skills. This research underscores the importance of interactive and enjoyable learning methods, as well as the application of positive reinforcement principles to support the development of early childhood skills.